An overview of Candida auris in Iraq: the silent killer (Acta Scientiarum. Biological Sciences, 2023)
Candida auris is an emerging pathogen known for its high mortality compared to other fungal diseases in healthcare units. Since its initial description in Japan in 2009, C. auris has been reported worldwide, including in Middle Eastern countries. Iraq, one of the Middle Eastern countries, does not seem to have adequately addressed C. auris as a serious emergent pathogen in the healthcare units, especially since numerous healthcare facilities in the Middle Eastern region have reported C. auris infections. Additionally, this pathogen poses unique challenges in the area due to its ability to resist multiple antifungal agents, causing serious invasive infections with high mortality rates. Efforts to control C. auris in Middle Eastern countries have primarily focused on infection surveillance, implementing infection prevention and control measures, and developing regional guidelines for diagnosis and management. However, the challenges associated with its detection, including misidentification and a lack of standardized diagnostic methods, have complicated these efforts. Understanding the epidemiology and molecular characteristics of C. auris in the Middle East is crucial for effective management and control. In conclusion, the combination of its multidrug resistance, high mortality rate, and the challenges of detecting and treating C. auris requires immediate attention and the implementation of comprehensive surveillance and prevention strategies, especially in Iraq. Despite concerted efforts by health agencies and national authorities, Iraq lacks a comprehensive surveillance system and a clear strategy to combat this pathogen effectively, making this fungus a significant threat to Iraq's healthcare systems.